CLINICAL AND MORPHOLOGICAL ASPECTS OF BRONCHIECTATIC DISEASE (LITERATURE REVIEW) - Azamat Musakulovich Norzhigitov; Shavkat Erjigitovich Islamov (Scholar Express Journals, 2022)
The article presents the analysis of the literature data on investigation of clinical and functional consequences of bronchopulmonary dysplasia in children. Long-term disorders of respiratory function including impairment of bronchial patency, decrease of pulmonary diffusing capacity and bronchial hyperresponsiveness in such patients have been established. The need to investigate the clinical and morphological aspects has been noted
Keywords: Bronchiectasis; children; clinical and morphological characteristics.